1974
DOI: 10.1161/01.cir.50.6.1105
|View full text |Cite
|
Sign up to set email alerts
|

Further Observations on the Etiology of the Right Bundle Branch Block Pattern Following Right Ventriculotomy

Abstract: SUMMARYFifteen patients with various congenital heart defects were studied during open heart surgery in order to establish the precise mechanism by which a right ventriculotomy causes a right bundle branch block (RBBB) pattern on the scalar electrocardiogram (ECG). All required a right ventriculotomy for the correction of their defects. In each, the right ventriculotomy was carried out in steps, with incisions (3 to 7) of approximately 1 cm in length. Six simultaneous scalar ECG leads were recorded prior to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1975
1975
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(12 citation statements)
references
References 21 publications
(4 reference statements)
0
12
0
Order By: Relevance
“…RBBB has been considered a benign condition without any negative impact on the long-term prognosis; it appears that this concept must be Pediatr Cardiol 20:326-330, 1999 Pediatric Cardiology revised to some extent, considering that a very wide QRS complex has been recognized as a risk factor for malignant ventricular arrhythmias [20]. RBBB may be due to interruption of the bundle centrally during closure of the VSD; however, often it is caused by the right ventricular incision (so-called distal RBBB) [26,32]. The site of the block can be determined by endocardial electrophysiologic recordings [15,42].…”
Section: Conduction Disturbancesmentioning
confidence: 99%
“…RBBB has been considered a benign condition without any negative impact on the long-term prognosis; it appears that this concept must be Pediatr Cardiol 20:326-330, 1999 Pediatric Cardiology revised to some extent, considering that a very wide QRS complex has been recognized as a risk factor for malignant ventricular arrhythmias [20]. RBBB may be due to interruption of the bundle centrally during closure of the VSD; however, often it is caused by the right ventricular incision (so-called distal RBBB) [26,32]. The site of the block can be determined by endocardial electrophysiologic recordings [15,42].…”
Section: Conduction Disturbancesmentioning
confidence: 99%
“…The clinical observations of Gelband et al (2) and Krongrad et al (14) have suggested that the electrocardiographic pattern of right bundle branch block developed immediately after the right ventriculotomy incision. Because there was no associated injury to the ventricular septum with this incision, thereby excluding the possibility of central injury to the right bundle branch, the authors deduced that there was "peripheral" injury to the right bundle branch.…”
Section: Discussionmentioning
confidence: 99%
“…Because there was no associated injury to the ventricular septum with this incision, thereby excluding the possibility of central injury to the right bundle branch, the authors deduced that there was "peripheral" injury to the right bundle branch. Krongrad et al (14) suggested that the conduction defect was distal to the insertion of the terminal fascicles of the right bundle into the ventricular myocardium. The prognostic significance of "peripheral" right bundle branch block would thus be excellent because conduction through the proximal right bundle branch and its terminal fascicles would be normal.…”
Section: Discussionmentioning
confidence: 99%
“…13 In others, proximal interruption occurred when septal sutures were placed to close the interventricular septal defect,5' 1' and in still others, following isolated pulmonary infundibular resection. "3' 2 In short, the right bundle branch may be injured along its entire course when open heart surgery is carried out in its proximity.…”
mentioning
confidence: 99%
“…However, the identification of the precise location of injury is more complex in cases in which several procedures that may cause a right bundle branch block were carried out, such as in patients with tetralogy of Fallot who had a right ventriculotomy and ventricular septal defect closure and infundibular resection. In such patients injury to the right bundle branch may occur as an isolated or combined lesion with each of the surgical procedures.8 13 The effect of the surgically created right bundle branch block pattern on long-term prognosis is unknown. It can be assumed reasonably that prognosis is related to the location of injury.…”
mentioning
confidence: 99%